Hepatopancreatoduodenectomy for advanced biliary malignancies. Issue 23 (5th December 2022) - Wu, Xiangsong; Li, Maolan; Wu, Wenguang; Wang, Xu'an; Li, Huaifeng; Bao, Runfa; Shu, Yijun; Shen, Jun; Gu, Jun; Wang, Xuefeng; Gong, Wei; Peng, Shuyou; et al.
Abstract: Background: Hepatopancreatoduodenectomy (HPD) has been considered the only curative treatment for metastatic cholangiocarcinoma and some locally advanced gallbladder cancers (GBCs). However, HPD has not yet been included in treatment guidelines as a standard surgical procedure in consideration of its morbidity and mortality rates. The aim of this study was to evaluate the safety and effectiveness of HPD in treating biliary malignancies. Methods: The medical records of 57 patients with advanced biliary cancer undergoing HPD from January 2009 to December 2019 were retrospectively retrieved. A case-control analysis was conducted at our department. Patients with advanced GBC who underwent HPD (HPD-GBC group) were compared with a control group (None-HPD-GBC group). Baseline characteristics, preoperative treatments, tumor pathologic features, operative results, and prognosis were assessed. Results: Thirteen patients with cholangiocarcinoma and 44 patients with GBC underwent HPD at our department. Significant postoperative complications (grade III or greater) and postoperative pancreatic fistula were observed in 24 (42.1%) and 15 (26.3%) patients, respectively. One postoperative death occurred in the present study. Overall survival (OS) was longer in patients with advanced cholangiocarcinoma than in those with GBC (median survival time [MST], 31 months vs . 11 months; P < 0.001). In the subgroup analysis of patients with advanced GBC, multivariate analysis demonstrated that T4 stage tumors ( P = 0.012), N2 tumors ( P = 0.001), and positive margin status ( P = 0.004) were independently associated with poorer OS. Patients with either one or more prognostic factors exhibited a shorter MST than patients without those prognostic factors ( P < 0.001). Conclusion: HPD could be performed with a relatively low mortality rate and an acceptable morbidity rate in an experienced high- volume center. For patients with advanced GBC without an N2 or T4 tumor, HPD can be a preferable treatment option.